PENGABDIAN MASYARAKAT BERUPA PELATIHAN DAN PEMBUATAN SISTEM SERAPAN AIR BIOPORI - Bahri, Asep Saepul; -, Adiran; Chandra, Yoga; Mamesah, Elli Diana; Rikmasari, Rima; Nugratama, Sony; Budianti, Yudi; Kusumawati, Mia (LPPM Universitas Islam 45 Bekasi, 2020)
Environmental problems are an important factor in life. One of the efforts to maintain the function of groundwater so that it is well preserved can be done by reforesting it and creating a household catchment area. One of them is by making infiltration holes to serve as temporary storage for rainwater and to maintain soil moisture during the dry season so as to prevent drought as well as during the rainy season to minimize flooding. The purpose of this training activity is to use land as a biopore water absorption system. While the purpose of this activity is to carry out the Tri Dharma of Higher Education in the form of Community Service. The results of the research that has been conducted by 8 members who will provide a way to make infiltration holes at SMPN 1 Setu and this service is carried out well.